HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN STUNTING PADA BADUTA DI KABUPATEN MAJENE - Wahdaniyah wahdaniyah; Nurpatwa Wilda Ningsi2; Diesna Sari Diesna Sari (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Stunting is a condition of failure to thrive in children under five (infants under five years old) due to chronic malnutrition so children are too short for their age. Stunting is one of the three global nutritional problems that is still became big responsibility for Indonesian government at this time to be resolved. Stunting in children under two has a higher risk when compared to other age groups because it will have a permanent impact on children's physical and cognitive development in the future. Poor household environmental sanitation conditions generally cause stunting prevalence to increase. The purpose of this study was to determine the relationship between environmental sanitation and the incidence of stunting in children under two in Pangali-Ali Village, Majene, West Sulawesi. This research is analytical research with observational approach by using a case-control design approach. The results showed that environmental sanitation was a risk factor for stunting where households with poor environmental sanitation were 2.94 times more at risk of stunting than those with good environmental sanitation (OR = 2.949, p = 0.022). The conclusion of this study reveals that there is a significant relationship between environmental sanitation and the incidence of stunting in children under two in Majene district